Non-State Actors and The Due Diligence Obligation to Protect Healthcare Facilities in Cyberspace: Is the World Prepared for The Next Pandemic? - Dr. Ardit Memeti (Pace International Law Review, 2026)
This article presents a novel approach by developing a lex specialis due diligence framework based on the elements identified in the ICJ Advisory Opinion on Climate Change, which by analogy, establishes sector-specific elements to protect healthcare facilities from cyberattacks by Non-State Actors (NSAs). Cyberattacks by NSAs during the COVID-19 pandemic exposed the risks, including the disruption of essential healthcare services and hindrance of positive obligations to ensure the rights to health, life, and privacy, among others. Existing instruments, including the Budapest Convention, the Tallinn Manuals, and the Oxford Statements, offer an important but incomplete framework. Meanwhile, the recent UN Convention Against Cybercrime (not yet in force) represents another missed opportunity to clarify due diligence obligations regarding the actions of NSAs targeting critical infrastructure, such as healthcare facilities. Therefore, this research highlights the inadequacy of simply extending general international law to cyberspace and argues in favor of establishing a sector-specific due diligence framework to protect healthcare facilities from cyberattacks by NSAs. Recent Ebola and hantavirus cases reinforce this conclusion.